Autism in 2016: the need for answers - Annio Posar; Paola Visconti (Elsevier, 2017)
Objective: Autism spectrum disorders are lifelong and often devastating conditions that severely affect social functioning and self-sufficiency. The etiopathogenesis is presumably multifactorial, resulting from a very complex interaction between genetic and environmental factors. The dramatic increase in autism spectrum disorder prevalence observed during the last decades has led to placing more emphasis on the role of environmental factors in the etiopathogenesis. The objective of this narrative biomedical review was to summarize and discuss the results of the most recent and relevant studies about the environmental factors hypothetically involved in autism spectrum disorder etiopathogenesis. Sources: A search was performed in PubMed (United States National Library of Medicine) about the environmental factors hypothetically involved in the non-syndromic autism spectrum disorder etiopathogenesis, including: air pollutants, pesticides and other endocrine-disrupting chemicals, electromagnetic pollution, vaccinations, and diet modifications. Summary of the findings: While the association between air pollutants, pesticides and other endocrine-disrupting chemicals, and risk for autism spectrum disorder is receiving increasing confirmation, the hypothesis of a real causal relation between them needs further data. The possible pathogenic mechanisms by which environmental factors can lead to autism spectrum disorder in genetically predisposed individuals were summarized, giving particular emphasis to the increasingly important role of epigenetics. Conclusions: Future research should investigate whether there is a significant difference in the prevalence of autism spectrum disorder among nations with high and low levels of the various types of pollution. A very important goal of the research concerning the interactions between genetic and environmental factors in autism spectrum disorder etiopathogenesis is the identification of vulnerable populations, also in view of proper prevention. Resumo: Objetivo: Os transtornos do espectro autista (TEAs) são vitalícios e normalmente são doenças devastadoras que afetam gravemente o funcionamento social e a autossuficiência. A etiopatogenia é presumivelmente multifatorial, resultante de uma interação muito complexa entre fatores genéticos e ambientais. O aumento drástico na prevalência de TEAs observado nas últimas décadas levou à maior ênfase no papel dos fatores ambientais na etiopatogenia. O objetivo desta análise da narrativa biomédica foi resumir e discutir os resultados dos estudos mais recentes e relevantes sobre os fatores ambientais hipoteticamente envolvidos na etiopatogenia dos TEAs. Fontes: Foi realizada uma pesquisa na Biblioteca Nacional de Medicina dos Estados Unidos (PubMed) sobre os fatores ambientais hipoteticamente envolvidos na etiopatogenia dos TEAs não sindrômicos, incluindo: poluentes atmosféricos, pesticidas e outros desreguladores endócrinos, poluição eletromagnética, vacinas e alterações na dieta. Resumo dos achados: Embora a associação entre poluentes atmosféricos, pesticidas e outros desreguladores endócrinos e o risco de TEA esteja recebendo cada vez mais confirmações, a hipótese de uma relação causal real entre eles ainda precisa de mais dados. Os possíveis mecanismos patogênicos por meio dos quais os fatores ambientais podem causar TEA em indivíduos geneticamente predispostos foram resumidos, com ênfase especial no papel cada vez mais importante da epigenética. Conclusões: Futuras pesquisas devem investigar se há uma diferença significativa na prevalência de TEA entre nações com níveis altos e baixos de vários tipos de poluição. Um objetivo muito importante da pesquisa a respeito das interações entre fatores genéticos e ambientais na etiopatogenia do TEA é a identificação de populações vulneráveis, também em virtude da prevenção adequada. Keywords: Autism spectrum disorder, Neurobiology, Epidemiology, Environmental factors, Air pollutants, Epigenetics, Palavras-chave: Transtorno do espectro autista, Neurobiologia, Epidemiologia, Fatores ambientais, Poluentes atmosféricos, Epigenética